2001
DOI: 10.2337/diabetes.50.5.1214
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphism Screening of Four Genes Encoding Advanced Glycation End-Product Putative Receptors

Abstract: Advanced glycation end-products (AGEs) may play an important role in the pathogenesis and progression of cardiovascular and renal complications of diabetes. Four putative AGE receptors (RAGEs), AGE-R1, AGE-R2, and AGE-R3 have been described. In this study, we scanned the sequence of the genes encoding these AGE receptors in 48 patients with type 1 diabetes and investigated the identified polymorphisms (n ‫؍‬ 19) in 199 type 1 diabetic patients with nephropathy and 193 type 1 diabetic patients without nephropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 28 publications
3
38
1
1
Order By: Relevance
“…The nucleotide changes between chromosome 6 and 3 included a C (chromosome 6) to A (chromosome 3) change at Ϫ1139/ϩ2298, reported as a polymorphism by Poirier et al (11). To verify our results and confirm the Ϫ1139/ϩ2298 C/A gene:pseudogene difference, we performed a PCR-RFLP study on the pseudogene polymorphisms we detected.…”
Section: Variations In Rage 5 Regulatory Region and ⌿Pbx2supporting
confidence: 70%
See 2 more Smart Citations
“…The nucleotide changes between chromosome 6 and 3 included a C (chromosome 6) to A (chromosome 3) change at Ϫ1139/ϩ2298, reported as a polymorphism by Poirier et al (11). To verify our results and confirm the Ϫ1139/ϩ2298 C/A gene:pseudogene difference, we performed a PCR-RFLP study on the pseudogene polymorphisms we detected.…”
Section: Variations In Rage 5 Regulatory Region and ⌿Pbx2supporting
confidence: 70%
“…We have identified variants of RAGE in the coding region resulting in amino acid changes (9) and, more recently, we identified eight novel polymorphisms in the 5Ј regulatory region of RAGE, which we confirmed to be on chromosome 6 (10). A recent study identified a polymorphism causing a change from C to A in the duplicated region at Ϫ1139 (numbered as Ϫ1152 by Poirier et al [11] from the translational start site); however, our own chromosome 6 -specific data did not support Ϫ1139 C/A as a polymorphism of RAGE (10). Therefore, characterization of both this anomaly and the ⌿PBX2 and RAGE/PBX2 loci are needed.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…In that study by Poirier et al, evidence of nominal association (p=0.041) between the glutamic acid repeats in PRKCSH and diabetic nephropathy was detected in a sample of 199 cases and 193 controls [7]. We analysed PRKCSH in a larger sample set and using a denser set of markers, but found no association with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 75%
“…Variations in the RAGE gene have been identified and screened for association with DR and other diseases. [31][32][33] Of the many polymorphisms that have been screened, the À429 and À374 are considered important, since these polymorphisms are reported to increase the RAGE gene transcript, which will augment increased AGE binding to cells and as a result lead to an altered signaling cascade. The G82S polymorphism has also been studied in various populations, which is yet another important polymorphism previously studied in this population.…”
Section: Discussionmentioning
confidence: 99%